The Role of Higher Education Institutes Offering Online Degrees in Democratizing Higher Education in India: Aligning with NEP-2020 (Bhartiya Knowledge Systems, 2024)
The study examines the significant role of HEIs offering online degrees in ach democratize higher education through technology. It explores how online platforms enhance access, reduce entry barriers, and promote equitable education. The emergence of these institutions is highlighted as a response to COVID research assesses the positive impact of online education on learner motivation and self addressing traditional education's limitations. It reviews policy recommendations and UGC guidelines for establishing and regulating HEIs offering online degrees in India. Key components include admission criteria, learning management systems, curriculum, virtual classrooms, teaching methodologies, assessment, student support, and program outcomes. Ethical consideratio strategies to address potential discrepancies in online education are also discussed. The study concludes by analyzing the prospects and limitations of HEIs offering online degrees in India, emphasizing their potential to improve accessibility, flex technologies in education, aligning with NEP-2020 goals.